#### Answer

$\sqrt[12] x$

#### Work Step by Step

$\dfrac{\sqrt[3] x}{\sqrt[4] x}=\dfrac{x^{1/3}}{x^{1/4}}=x^{1/3-1/4}=x^{1/12}=\sqrt[12] x$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$\sqrt[12] x$

$\dfrac{\sqrt[3] x}{\sqrt[4] x}=\dfrac{x^{1/3}}{x^{1/4}}=x^{1/3-1/4}=x^{1/12}=\sqrt[12] x$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.